2013
DOI: 10.1111/ecc.12068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise on angiogenesis and apoptosis-related molecules, quality of life, fatigue and depression in breast cancer patients

Abstract: The aim of this study was to explore the effects of exercise on angiogenesis and apoptosis-related molecules, quality of life, fatigue and depression in patients who completed breast cancer treatment. Sixty breast cancer patients were randomised into three groups, as supervised exercise group, home exercise group and education group. Angiogenesis and apoptosis-related cytokine levels and quality of life (EORTC QOL-C30: European Organisation for Research and Treatment of Cancer Quality of Life C30), fatigue (Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 51 publications
(116 reference statements)
1
87
0
3
Order By: Relevance
“…Of the sixteen studies involving patients in active treatment [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] , six demonstrated that, compared with the control group, the intervention group experienced significant improvements in qol 30,31,33,[38][39][40]43 . In the thirteen post-treatment intervention studies 10,12,14,[45][46][47][48][49][50][51][52][53][54] , two reported similar significant differences between groups 46,49 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…Of the sixteen studies involving patients in active treatment [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] , six demonstrated that, compared with the control group, the intervention group experienced significant improvements in qol 30,31,33,[38][39][40]43 . In the thirteen post-treatment intervention studies 10,12,14,[45][46][47][48][49][50][51][52][53][54] , two reported similar significant differences between groups 46,49 .…”
Section: Quality Of Lifementioning
confidence: 99%
“…Of the sixteen rcts involving patients in active treatment [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] , seven reported significant differences between the intervention and control groups (Table vi) 23,24,26,[31][32][33]36 . In the thirteen posttreatment intervention studies [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] , two reported significant qol improvement in the exercise groups 41,42 . In particular, patients with lymphedema experienced qol benefits, and aerobic and resistance exercises were both safe for women who had undergone breast and axillary surgery 6,7,38,39,44 .…”
Section: Qol and Muscular And Aerobic Fitnessmentioning
confidence: 99%
“…One systematic review 20 found that cardiopulmonary exercise testing was a safe, noninvasive method to measure cardiopulmonary fitness in people living with cancer, both during and after treatment. Seventeen rcts [22][23][24]27,29,[30][31][32][33]37,39,42,45,47,[51][52][53] found that no adverse events or side effects were attributable to the exercise program. Seven 26,28,34,35,40,46,50 did not report on adverse events at all.…”
Section: Commentsmentioning
confidence: 99%
“…In this review, we have summarized a collection of various population-based studies on breast cancer and PA, and compared the beneficial effect of exercise on cancer such as the cancer type, duration, intensity, and timing of exercise (before diagnosis, after diagnosis, or during treatment) ( Table 2) [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. Numerous studies have suggested that PA prior to breast cancer diagnosis was significantly beneficial for the patient's treatment outcome and survival [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92]. For example, a group of researchers performed a prospective cohort study in Germany which included 3,393 non-metastatic breast cancer patients: the mortality of breast cancer was significantly and inversely associated with prediagnosis recreational PA [77].…”
Section: Breast Cancer and Physical Activity (Pa)mentioning
confidence: 99%
“…Some studies have investigated whether exercise can modulate circulating proinflammatory cytokines, such as IL-1β, IL-2, IL-4, macrophage inflammatory protein-1 beta (MIP-1β), and tumor necrosis factor alpha (TNF-α) [92,108,109], suggesting a protective effect of exercise on inflammation perturbation following cancer treatment. A systematic review suggests that physical exercise can lead to changes in a variety of immune system parameters, including lymphocyte function such as improved cytotoxic activity by natural killer (NK) cells and proliferation of granulocytes [110].…”
Section: Inflammatory Reactionsmentioning
confidence: 99%